Determination of Consumer Purchase Thresholds for Discoloration of Beef Strip Steaks in Retail Display - Stephanie L. Witberler; Lauren M. Frink; Mason J. Prester; Chesney A. Effling; Michael D. Chao; Morgan D. Zumbaugh; Jessie L. Vipham; Erin S. Beyer; Travis G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: The objectives of this study were to determine the consumer purchase threshold for discoloration of beef steaks in a simulated retail display and to determine the best objective measurement to predict consumer purchase intent. Study Description: Steaks from 0% to 100% discoloration were evaluated by trained panelists and consumer panelists in a simulated retail display. Trained panelists scored percent discoloration, redness, and fat color, while consumer panelists were asked to rate the sample appearance and then asked if they would purchase the sample at full price and at a discounted rate. L* (lightness), a* (redness), b* (yellowness), and spectral data were collected and hue angle, chroma, and percent deoxymyoglobin, metmyoglobin, and oxymyoglobin were calculated. Results: The a* values were a good objective predictor of purchase intent (R2 = 0.64 full-priced and R2 = 0.56 for discounted; P < 0.05). At full price, a* values of 25.3, 29.9, 34.4, and 37.6 corresponded to a 50%, 75%, 90%, and 95% likelihood to purchase, whereas if the product was discounted, a* values of 20.3, 25.8, 31.3, and 35.0 corresponded to those same thresholds. Trained sensory panel redness scores were also a good predictor of consumer purchase intent with R2 = 0.64 full-priced and R2 = 0.59 discounted (P < 0.05). At full price, trained redness scores of 68.0 and 86.3 corresponded to a 50% and 75% likelihood to purchase, whereas if the product was discounted, trained redness scores of 46.8, 68.8, and 90.8 corresponded to 50%, 75%, and 90% thresholds. The Bottom Line: The a* value and trained panel redness score are good indicators of consumer purchase intent, showing that consumers highly value redness when choosing steaks.
Keywords: consumer; discoloration; retail